2019
DOI: 10.3390/w11050889
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Control of Underground Rivers by Reverse Faults in Tunnel Site and Selection of Tunnel Elevation

Abstract: Along with the need for western economic development, the number of long tunnel projects which go through mountains is constantly on the rise. In the process of construction, various disaster-causing structures are frequently exposed, which leads to many geological disasters. The traditional idea is that the reverse fault is not easily developed for an underground river, which means that the tunnel elevation design is not considered adequately. When some tunnels cross the bottom of the river, the fractures nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Culverts-Small passages allowing watercourses to pass under railway tracks, including underground rivers [235]. Old masonry culverts particularly can be weakened by solution and hydraulic action resulting in partial section collapse, deforming the railbed above and causing water backlog which floods tunnels.…”
Section: Common Assets In Masonry Railway Tunnelsmentioning
confidence: 99%
“…Culverts-Small passages allowing watercourses to pass under railway tracks, including underground rivers [235]. Old masonry culverts particularly can be weakened by solution and hydraulic action resulting in partial section collapse, deforming the railbed above and causing water backlog which floods tunnels.…”
Section: Common Assets In Masonry Railway Tunnelsmentioning
confidence: 99%
“…Groundwater inrush is a typical hydrologic natural hazard connected with mining activities. Groundwater inrush hazards from a grouted karst collapse pillar in longwall mining were investigated by Ma et al [17]. The karst collapse pillar represents a common geological structure in northern China coalfields, often acting as an important groundwater inrush pathway in underground mining as it contains a significant number of granular rocks, which can easily migrate under high hydraulic pressure.…”
Section: Tunneling and Engineering Mining Inrushmentioning
confidence: 99%
“…A mechanical model with a floor-pillar-roof system was established, followed by a numerical model to evaluate the continuous instability and groundwater inrush risk. The criteria for the system stability assessment were defined based on comparison of the collective energy and stiffness in the floor-pillar-roof system [17], aimed at eliminating groundwater inrush hazards in coal mines which, in the past, were responsible for casualties in the hundreds of miners.…”
Section: Tunneling and Engineering Mining Inrushmentioning
confidence: 99%
“…The related disasters are mainly characterized by climatic instantaneous discharge of water and mud inrush, with great suddenness, high frequency, and great severity [29]. The scale of water inrush caused by underground rivers is large, and the disaster is catastrophic because underground rivers are rich in water sources and greatly affected by rainfall [30]. Li et al [31] studied the major water and mud inrush disasters in Lingjiao Tunnel and concluded that the water-bearing and mud-filled structure was the fracture-induced karstified zone rather than the main fault area.…”
Section: Introductionmentioning
confidence: 99%